Analysis of surface integrity for minimum quantity lubricant - MQL in grinding - da Silva, Leonardo Roberto; Bianchi, Eduardo Carlos; Fusse, Ronaldo Yoshinobu; Catai, Rodrigo Eduardo; Franca, Thiago Valle; Aguiar, Paulo Roberto (Elsevier B.V., 2007)
The quality of machined components is currently of high interest, for the market demands mechanical components of increasingly high performance, not only from the standpoint of functionality but also from that of safety. Components produced through operations involving the removal of material display surface irregularities resulting not only from the action of the tool itself, but also from other factors that contribute to their superficial texture. This texture can exert a decisive influence on the application and performance of the machined component. This article analyzes the behavior of the minimum quantity lubricant (MQL) technique and compares it with the conventional cooling method. To this end, an optimized fluid application method was devised using a specially designed nozzle, by the authors, through which a minimum amount of oil is sprayed in a compressed air flow, thus meeting environmental requirements. This paper, therefore, explores and discusses the concept of the MQL in the grinding process. The performance of the MQL technique in the grinding process was evaluated based on an analysis of the surface integrity (roughness, residual stress, microstructure and microhardness). The results presented here are expected to lead to technological and ecological gains in the grinding process using MQL. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: surface integrity; minimum quantity lubricant (MQL); nozzle and grinding